Offspring chemical control of adult reproductive transitions in a social insect - Baptiste Piqueret; Jerrit Weissflog; Sandra Tretter; Tim Zetzsche; Daniel Veit; Stefan Bartram; Rayko Halitschke; Yuko Ulrich (Proceedings of the National Academy of Sciences, 2026)
Parental care enhances offspring survival and growth but often entails a trade-off in which caregivers temporarily suppress their own reproduction to invest in existing young. In vertebrates, these parental reproductive cycles are controlled by offspring-derived cues that reduce or suppress parental fertility. While many insects display obligate parental care, the role of offspring cues in regulating adult reproduction remains unresolved outside advanced eusocial taxa, where reproductive cycles have largely been lost. Here, we investigate reproductive cycles in the clonal raider ant Ooceraea biroi , in which totipotent females alternate between caring for larvae and laying eggs. Using custom behavioral assays, we show that larvae inhibit adult reproduction without physical contact, implicating volatile cues. Chemical analyses identified a previously undescribed larva-specific compound, methyl 3-ethyl-2-hydroxy-4-methylpentanoate (MEHMP), which is absent from other developmental stages and ant species. Exposure to synthetic MEHMP recapitulated the inhibitory effect of larval volatiles, confirming its role as a pheromone that suppresses adult egg laying. Our findings demonstrate that ant larvae produce a pheromone that suppresses adult reproduction, providing a direct chemical link between offspring presence and parental reproductive suppression, and underscoring the central role of offspring signals in mediating parental reproductive investment in animals that care for their young.